Associations between measures of central adiposity and periodontitis among older adults. Issue 2 (7th September 2013) - Muñoz‐Torres, Francisco J.; Jiménez, Monik C.; Rivas‐Tumanyan, Sona; Joshipura, Kaumudi J.
Abstract Objective To evaluate the association between measures of adiposity and periodontitis among older Puerto Rican adults. Methods A cross‐sectional study was conducted among 147 representative adults ≥70 years living in the San Juan metropolitan area. Height, weight, waist circumference (WC), and hip circumference were measured by trained personnel. Periodontal probing depth and attachment loss (AL) were measured by calibrated examiners. Periodontitis was classified according to the Center for Disease Control/American Academy of Periodontology (CDC‐AAP) definitions and using tertiles of mean AL and percent of sites with AL ≥3 mm. Multivariable polytomous logistic regression models adjusted for age, gender, smoking, education, diabetes status, physical activity, and total fruit and vegetable intake were used to model associations between WC, waist‐to‐hip ratio (WHR), and periodontitis. Results High WC (men: ≥102 cm versus <102 cm, women: ≥88 cm versus <88 cm) compared with normal showed nonsignificant associations with severe (OR = 2.56, 95% CI: 0.76–8.67), moderate periodontitis (OR = 1.53, 95% CI: 0.65–3.60), and upper tertile of mean AL (OR = 2.28, 95% CI: 0.83–6.23). Elevated WHR versus normal (men: ≥0.95 versus <0.95, women: ≥0.88 versus <0.88) was associated with moderate periodontitis (OR = 2.36, 95% CI: 1.01–5.52) and showed a borderline significant association with the upper tertile of mean AL (OR = 2.52, 95% CI: 0.96–6.63, P = 0.06). Conclusions Central adiposity was associated with a greater risk of periodontitis in this population of older adults, although analyses were underpowered. These results hold important public health implications given the high prevalence of adiposity and periodontitis among older adults.